The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.3109/09273948.2010.486099
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Panuveitis following Intravesical BCG Immunotherapy for Bladder Carcinoma

Abstract: Ocular inflammations following BCG therapy for bladder cancer are rare, and little is known about the management of such cases. This is the first report of bilateral panuveitis with optic nerve edema following such treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Ocular toxicity like bilateral uveitis,[16] endophthalmitis,[7] choroiditis,[8] chorioretinitis,[9] granulomatous uveitis, endogenous endophthalmitis with B\L infiltrative retinitis, and vitritis[5] have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ocular toxicity like bilateral uveitis,[16] endophthalmitis,[7] choroiditis,[8] chorioretinitis,[9] granulomatous uveitis, endogenous endophthalmitis with B\L infiltrative retinitis, and vitritis[5] have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Ocular complications such as keratitis, uveitis,[1] conjunctivitis,[4] autoimmune retinopathy,[5] panuveitis,[6] endophthalmitis,[7] choroiditis,[8] and chorioretinitis[9] have been documented.…”
Section: Introductionmentioning
confidence: 99%
“…International Immunopharmacology j o u r n a l h o m e p a g e : w w w. e l s ev i e r. c o m / l o c a t e / i n t i m p some research has reported [15,16] that some patients developed complications after intravesical instillation of BCG: high temperature followed by hematuria or granulomatous prostatitis, epidydimoorchitis, urethral obstruction and so on. Muramyl dipeptide (N-acetyl-muramyl-L-Ala-D-isoGln, MDP) is the minimal essential structure of the mycobacterial cell wall in Freund's complete adjuvant.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 97%
“…However, BCG is still widely and successfully used as local treatment for bladder carcinomas. Several cases of uveitis as side effects of BCG instillation are reported in the literature (Uppal et al, 2010). The group of Wildner described a patient who presented with bilateral granulomatous iritis 2 weeks after she developed cystitis from BCG-instillation to treat her bladder carcinoma.…”
Section: Interplay Between Innate and Adaptive Immunity In The Devmentioning
confidence: 99%